Supramolecular protein cages constructed from a crystalline protein matrix. Issue 16 (6th February 2018) - Negishi, Hashiru; Abe, Satoshi; Yamashita, Keitaro; Hirata, Kunio; Niwase, Kento; Boudes, Marion; Coulibaly, Fasséli; Mori, Hajime; Ueno, Takafumi
Abstract : Protein cages were constructed by cross-linking monomers in polyhedra crystals, followed by dissolution of the crystals. Abstract : Protein crystals are formed via ordered arrangements of proteins, which assemble to form supramolecular structures. Here, we show a method for the assembly of supramolecular protein cages within a crystalline environment. The cages are stabilized by covalent cross-linking allowing their release via dissolution of the crystal. The high stability of the desiccated protein crystals allows cages to be constructed.